REBA: An Ergonomics Assessment for Machine Operator of Porang (Amorphophallus Muelleri) - Eko Nurmianto; Arino Anzip; Dwi Endah Kusrini (Institut Teknologi Sepuluh Nopember, 2020)
This Rapid Entire Body Assessment (REBA) has been applied for assessing operator of porang cutting machine in agriculture/forestry. An ergonomic team, industrial engineering, mechanical engineering, chemical engineering and business statisticians test the porang (amorphophallus muelleri) cutting machine and collect individually data more than 10 examples of postures to produce a new evaluation that combines dynamic and static posture loading factors, human load interfaces (couplings), and new limb concepts the assisted gravity. position. Initial reliability for inter-observer coding shows hope, but further work is needed to establish the trust for the machinery customer.